Health assessment of araucaria columnaris and yucca aloifolia in UNIMAS - Nur Fatihah, Khair Yusof (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Urban trees planted in the urban landscape are usually beatiful, of high aesthetic values and should be free of pests and diseases. However, due to several abiotic and biotic factors, trees are sometimes infected with diseases and pests. In this study, the main objective is to assess the health status of Araucaria columnaris and Yucca aloifolia planted in UNIMAS campus and to identify the types of diseases associated with Araucaria columnaris and Yucca aloifolia.